Bases para amazonizar: um estudo sobre a formação de professores em cursos de Letras-Libras na Amazônia - Mendonça, Carla Andréa Sampaio (Universidade Federal de São Carlos, 2026)
This doctoral thesis focuses on teacher education in the undergraduate Letras-Libras (Brazilian Sign Language) teacher training programs offered by federal universities in the Brazilian Amazon. It is based on the recognition that teacher education aimed at the educational inclusion of deaf students in this regional context requires consideration of the linguistic, cultural, social, geographic, and socio-environmental particularities that characterize the multiple Amazons. The central objective of this research is to analyze the advances, challenges, and possibilities for improving the training offered in Letras-Libras undergraduate teacher education programs at federal universities in the Brazilian Amazon, considering the diverse linguistic, cultural, and socio-environmental dimensions of the region that shape and permeate the lives of deaf individuals and that are either present or silenced within these educational processes.The research adopts a qualitative approach and was developed through two complementary studies. Study I consisted of a systematic literature review aimed at mapping and characterizing the scientific production concerning initial teacher education in undergraduate teaching programs in the Amazon region, outlining the institutional, pedagogical, political, and socio-environmental context in which the Letras-Libras programs are situated. Study II was based on focus groups conducted with coordinators, professors, and students from Letras-Libras undergraduate teacher education programs, seeking to understand, from their perspectives, the elements that configure the advances, limitations, and possibilities for improving this training. Data analysis was carried out in light of the theoretical framework of Bakhtin and the Bakhtin Circle, mobilizing analytical categories such as dialogism, utterance, verbal interaction, meaning and theme, ideological sign, alterity, discourse, ideology, exotopy, and responsive act. These concepts enabled the identification of the meanings circulating in the participants’ utterances, highlighting the polyphonic and conflictive nature of discourses surrounding teacher education and revealing the need for a dialogical curricular construction that is responsive to the linguistic and socio-environmental realities of the Amazon.In summary, the results indicate that despite structural limitations, weaknesses in public policies, and processes of curricular homogenization, there are emerging movements of resistance, institutional initiatives, and formative experiences that point to the possibility of a more dialogical, territorially grounded, and socially responsive teacher education, sensitive to the multiple deaf identities present in the region.
Bases for amazonizing: a study about teacher formation in Letras-Libras courses in the Amazon
Keywords: Educação especial; Formação de professores na Amazônia; Cursos de Letras-Libras; Special education; Teacher Education in the Amazon; Letras-Libras Programs; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades